The role of translation and interpretation in facilitating inter-organisational knowledge transfer - Cranefield, Jocelyn; Pak, Yoong (2006)
This paper reports on the results of a larger research project that investigated the factors impacting on inter-organisational transfer in the New Zealand State Sector. Seven gatekeepers (boundary-spanning individuals) from different organisations were interviewed about their experiences in facilitating the transfer of a new strategic knowledge model between organisations.The context for the research was an inter-organisational project concerned with the development and adoption of an emergent model for strategic management in the State Sector (Managing for Outcomes).A range of factors that facilitated inter-organisational knowledge transfer were identified. Among these, the activities of translation and interpretation were found to be critical to the successful transfer of the emergent knowledge model.Gatekeepers reported performing ongoing translation and interpretation duties, requiring specialised skills, during the course of the project. The nature of these activities is outlined, with reference to a staged model for knowledge transfer that emerged from the research project.Implications for research and practice are then outlined.